Tank contamination and simulated drift effects of dicamba-containing formulations on soybean cultivars - Alves, Guilherme S.; Vieira, Bruno C.; Ynfante, Rosa S.; Santana, Thalyson M. [UNESP]; Moraes, Jesaelen G.; Golus, Jeffrey A.; Kruger, Greg R. (Wiley, 2020)
The objectives of this study were to (a) investigate the spray drift potential of dicamba (3,6-dichloro-2-methoxybenzoic acid) formulations with different nozzles in a low-speed wind tunnel and (b) evaluate the effects of sublethal rates of dicamba-containing formulations on non–dicamba-tolerant (DT) soybean [Glycine max (L.) Merr.] cultivars. The dicamba formulations used were diglycolamine (DGA), N,N-Bis-(3-aminopropyl)methylamine, and diglycolamine with VaporGrip (DGAvg). The wind tunnel drift study was conducted with these three dicamba formulations, two nozzle types (AIXR110015 and TTI110015), and five downwind distances from the nozzle (1, 2, 4, 8, and 12 m). The dicamba rate was 560 g ae ha−1, simulating a 140 L ha−1 carrier volume. The soybean exposure study was conducted in two experimental runs with three sublethal dicamba rates (0.112, 0.56, and 5.6 g ae ha−1), the three dicamba formulations aforementioned, and five non-DT soybean cultivars (Asgrow A3253, Asgrow AG2636, Credenz CZ2601LL, DynaGro 39RY25, and Hoegemeyer 2511NRR). Applications were made using a spray chamber with a single AI9502EVS even nozzle that delivered 140 L ha−1. During applications, soybean plants were at three-leaf growth stage. Dicamba formulations had different drift deposition across the AIXR and TTI nozzles. The soybean cultivars had different levels of sensitivity to dicamba and depended on rate vs. formulation interaction. The DGA caused greater biomass reduction on soybean cultivars compared with DGAvg, especially for Credenz CZ2601LL, which was one of the most dicamba-sensitive cultivars along with Hoegemeyer 2511NRR. Additional care must be taken to mitigate off-target movement from dicamba applications with these cultivars nearby.